Potentiometric and HPLC Methods for the Determination of Meloxicam in Bulk and Drug Formulations. Issue 1 (2012) - El-Ries, Mohammed A.; El-Dars, Farida; Attia, Fekria M. Abou; Farag, A.B.; El-Hamed, Ayat M. Abd
No abstract available